Processes Contributing to Resilience of Coastal Wetlands to Sea-Level Rise - Stagg, Camille L.; Krauss, Ken W.; Cahoon, Donald R.; Cormier, Nicole; Conner, William H.; Swarzenski, Christopher M. (Ecosystems (New York), 2016)
The objectives of this study were to identify processes that contribute to resilience of coastal wetlands subject to rising sea levels and to determine whether the relative contribution of these processes varies across different wetland community types. We assessed the resilience of wetlands to sealevel rise along a transitional gradient from tidal freshwater forested wetland (TFFW) to marsh by measuring processes controlling wetland elevation. We found that, over 5 years of measurement, TFF2Ws were resilient, although some marginally, and oligohaline marshes exhibited robust resilience to sea-level rise. We identified fundamental differences in how resilience is maintained across wetland community types, which have important implications for management activities that aim to restore or conserve resilient systems. We showed that the relative importance of surface and subsurface processes in controlling wetland surface elevation change differed between TFFWs and oligohaline marshes. The marshes had significantly higher rates of surface accretion than the TFFWs, and in the marshes, surface accretion was the primary contributor to elevation change. In contrast, elevation change in TFFWs was more heavily influenced by subsurface processes, such as root zone expansion or compaction, which played an important role in determining resilience of TFFWs to rising sea level. When root zone contributions were removed statistically from comparisons between relative sea-level rise and surface elevation change, sites that previously had elevation rate deficits showed a surplus. Therefore, assessments of wetland resilience that do not include subsurface processes will likely misjudge vulnerability to sealevel rise.